Factors affecting the outcomes in patients with acute respiratory distress syndrome in a tertiary care setting - Muhammed Rashid; Manasvini Ramakrishnan; Deepa Sudalai Muthu; Viji Pulikkel Chandran; Girish Thunga; Vijayanarayana Kunhikatta; Vishal Shanbhag; Raviraja V. Acharya; Sreedharan Nair (Elsevier, 2022)
Purpose: The clinical profile and factors affecting outcomes in acute respiratory distress syndrome (ARDS) from adequately sample-sized Indian studies are still lacking. We aimed to investigate the clinical profile, treatment pattern, outcomes; and to assess factors affecting non-recovery in ARDS patients. Patients and methods: A retrospective observational study was conducted among adult ARDS patients admitted during five year period (January 2014-December 2018) in a South Indian tertiary care setting. The relevant data were collected from the medical records to the data collection form. The univariate and multivariate logistic regression analyses were conducted to identify the predictors of outcomes using SPSS v20. Results: A total of 857 participants including 496 males and 361 females with a mean age of 46.86 ± 15.81 years were included in this study. Fever (70.9%), crepitation (58.3%), breathlessness (56.9%), and cough (45%) were the major clinical presentation. Hypertension (25.2%), kidney disease (23.8%), and diabetes (22.3%) were the major comorbidities; and sepsis (37.6%), pneumonia (33.3%), and septic shock (27.5%) were the major etiological factors observed. Antibiotics and steroids were administered to 97.9% and 52.3% of the population, respectively. The recovery rate was 47.49%. The patients with scrub typhus, dengue, pancreatitis, and oxygen supplementation had significantly lower mortality. The factors such as advanced age, sepsis, septic shock, liver diseases, and ventilation requirements were observed to be the independent predictors of non-recovery in ARDS patients. Conclusion: A comparable recovery rate was observed in our population. Advanced age, sepsis, septic shock, liver diseases, and ventilation requirements were the independent predictors of non-recovery.